Animal welfare: children’s plural discourses in contexts of early childhood education - Tomás, Catarina (2020)
The present work is focused on the presentation of some results of a project developed about the social representations of children on animal welfare and animal rights (e.g., cultural demonstrations with animals, exhibition of animals in captivity, production and consumption of products of animal origin, treatment of pets and farm animals). They are preliminary results within the scope of a broader project "ANIMALIS - Animal welfare in pre-service kindergarten and primary school teachers' education. Using the Sociology of Childhood, Childhood Pedagogy, Environmental Education and Human-animal Studies, the present work aims to analyse children´s discourses associated with factors which can limit animal welfare and their rights and also to identify possibilities of educational intervention compatible with the inclusion of animals and their rights in pedagogical practices. These discourses started from the analysis and discussion of situations involving different animal uses present in the book of Patrick George “Animal Rescue” published by 2015. The methodological approach is based on a qualitative matrix with the adoption of data collection and analysis methodologies congruent with the object under study and with the epistemological assumptions of the sociological research with children: ethnographic observation, image collection, analysis of drawings, documentary analysis and focused discussion groups (book as an inducer of the discussion). The selection obeyed the criteria of identification of specificity, interest and feasibility of the research. The participants were four groups of children, between 2 and 5 years old, from three Kindergarten rooms (25 children each room) and one nursery room (12 children) of a private socio-educational organization in the city of Lisbon. The situations designed around animals, promoted by four educators with extensive professional experience, allowed to identify certain practices developed with animals (i) as problematic for children (e.g. abandonment and neglect of animals, sale of animals in stores, use of animal fur to make clothing and footwear) and (ii) as necessary (e.g., the need to invest more in promoting animal and nature rights, to reflect on the role of pets in their lives, and to develop projects to learn more about particular animals or situations involving them). The conflict between individual and group visions is a theme to be highlighted from the analysis of data as well as the fact that children in the nursery room reveal more blurred boundaries between the human and non-human worlds.